Measuring the Effect of using Two Carbon Sources (Sodium Bicarbonate with Rice Washing Water) on the Chemical Composition, Fatty Acids and Amino Acids of Marine Microalgae Nannochlorpsis Oceanica (Global Journal of Science Frontier Research, 2021)
Microalgae breeding media must be cost-effective, enable high growth, meet exact requirements and be readily available. The effect of different levels of sodium bicarbonate and rice wash water [25, 50, and 75%] in the growth medium on the biochemical constituents (protein, carbohydrates, lipids, fatty acids, and amino acids) of the Nannochloropsis oceanica was assessed compared to the F/2 Guillard standard medium. The obtained results revealed that the chemical constituents of Nannochloropsis oceanica affected by the level of urea used and the rice washing water. The highest protein, carbohydrate contents, and highest EAA (51.39%) obtained using ME1. medium (25% RWW and 75% SB) as compared to the control (100% F/2). The highest total lipid content was achieved by using the ME3 medium (75% RWW & 25% SB) producing (42.71 %), were the obtained the of the highest biomass productivity and lipid productivity in ME3 medium. In accordance, the highest total saturated fatty acids percentage (TSFA) of Nannochlorpsis oceanica recorded by ME3 medium.
Keywords: amino acids; fatty acids; nannochloropsis oceanica; proximate composition